Outcome of partial repair of massive rotator cuff tears with and without human tissue allograft bridging repair. Issue 1 (January 2017) - Pandey, Radhakant; Tafazal, Suhayl; Shyamsundar, Srinivasan; Modi, Amit; Singh, Harvinder Pal
Background: The surgical management of massive rotator cuff tears remains a challenge. It is suggested that, even in a massive tear that appears irreparable, attempting to repair it as much as possible can be helpful in improving functional outcomes. However the results can be short term and variable. The purpose of our study was to determine if human tissue allograft bridged repair of massive irreparable rotator cuff tears to achieve a complete repair produces similar outcomes compared to partial repair alone. Methods: We prospectively reviewed outcome scores in 13 patients who underwent partial repair alone for massive irreparable rotator cuff tears and compared them to 13 patients who had partial repairs bridged with allograft. Oxford and Constant scores were compared pre-operatively and at a minimum follow-up of 2 years (range 2 years to 5 years). Results: The mean improvement in the Constant score at final follow-up compared to pre-operative scores was 27.7 points in the partial repair group and 42.8 points in the allograft group ( p  < 0.01). The Oxford Shoulder Score improved mean of 19.3 points in the partial repair group and 29 points in the allograft group ( p  < 0.02) at 2 years. Conclusions: Human tissue matrix allograft provides a better outcome for open bridging of irreparable rotator cuff tears than partial repair alone.